Fairness and competition in a bilateral matching market - Helmut Bester (Freie Universität Berlin, School of Business & Economics, 2021)
This paper analyzes fairness and bargaining in a dynamic bilateral matching market. Traders from both sides of the market are pairwise matched to share the gains from trade. The bargaining outcome depends on the traders' fairness attitudes. In equilibrium fairness matters because of market frictions. But, when these frictions become negligible, the equilibrium approaches theWalrasian competitive equilibrium, independently of the traders' inequity aversion. Fairness may yield a Pareto improvement; but also the contrary is possible. Overall, the market implications of fairness are very different from its effects in isolated bilateral bargaining.
urn:nbn:de:kobv:188-refubium-31262-4
Keywords: C78; D5; D6; D83; D9; 330; Fairness; inequity aversion; bargaining; ultimatum game; matching market; search costs; competitive equilibrium